A Review of Medical Image Watermarking Schemes - Jasni, Mohamad Zain; Liew, Siau-Chuin (2009)
Medical images plays an important role for clinical purposes and medical science. Medical image can be modified easily with existing image processing tools available today. The usage of security measures such as watermarking can protect the integrity of the images. This paper will review and compare few watermarking schemes for the usage in medical imaging. The quality issues to be considered before a watermarking scheme is chosen for implementation into existing medical information system will be discussed